Detection of hpv-dn a and viral load associated to colposcopv as predictive fàctors of histological cervical lesion in women with atypical squamous cells (asc) in pap smear - Silva, Samara M.M da; Sarian, Luis Otávio Z.; Derchain, Sophie F.M.; Campos, Elisabete A.; Montemor, Eliana B.L.; Dufloth, Rozany M.; Zeferino, Luiz Carlos (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Introduction: Different diagnostic methods have been tested to assess what is the best way to detect CIN or câncer in women with ASC in the Pap smear. Objective: To analyse the role of HPV-DNA detection and viral load as predictive factor for biopsy confirmed cervical lesion in women with atypical squamous cells (ASC) in Pap smear. Methods: For thiscross seclional study 60 women with ASC in PAPsmear referred between February 2002 toJanuary 2003 were included, In all of them samples for Hybrid Capture II (HC II) were collected and colposcopy examination was done. Odds ratio were calculated for statistical analysis. Results: Among the studicd women, six women (10%) had CIN in biopsy - five CIN I and I CIN 2. HC II detected HPV DNA in 24 women with a médium viral load of 79 relative light unit (RLU). HPV-DNA detection rate was significantly higher in women aged 35 years old or less. Although five among the six cases with biopsy confirmed CIN had positive HC II. HPV-DNA detection was not significantly associated with histological lesion (OR 9.2; 95% 1C 0.9-224.0). Twenty-five women had abnormal findings at colposcopy examination and the main image was aceto white epithelia. Conclusion: There was a low proporlion of CIN in women with ASC in Pap smear. HC II was positive in five among the six women with biopsy confirmed CIN lesion.